2016
DOI: 10.1590/1678-4324-2016160151
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Status, Lipid Peroxidation and Testis-histoarchitecture Induced by Lead Nitrate and Mercury Chloride in Male Rats

Abstract: This study was done to evaluate the effects of lead nitrate and mercury chloride in testis tissues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…Dosing of heavy metals mixture produced lower level of glutathione peroxidase (GPx) in liver (p < 0.0001) and kidney (p < 0.001) tissues at heavy metals group in comparison with control group, this could probably due to the utilization of its defense mechanism against toxic metals within these organs as a result of ROS generation; such suggestion is matched with Ercal et al, (2001); Saxena et al, (2005) and Bas & Kalender (2016). However, rats that exposed to toxic metals and treated with propolis exhibited signi cant improving in the activities of GPx in livers (p < 0.001) as well kidney (p < 0.01) when compared with heavy metals group; that issue clarify the protective role of propolis in recovering the affected tissues of liver and kidney as healthy rats through reducing combined toxicity of investigated metals; these ndings were corroborated very well with Salama & El-Bahr, (2007);Bhadauria, (2012) and Mohamed et al, (2017).…”
Section: -4-antioxidant Enzymes and Propolissupporting
confidence: 67%
“…Dosing of heavy metals mixture produced lower level of glutathione peroxidase (GPx) in liver (p < 0.0001) and kidney (p < 0.001) tissues at heavy metals group in comparison with control group, this could probably due to the utilization of its defense mechanism against toxic metals within these organs as a result of ROS generation; such suggestion is matched with Ercal et al, (2001); Saxena et al, (2005) and Bas & Kalender (2016). However, rats that exposed to toxic metals and treated with propolis exhibited signi cant improving in the activities of GPx in livers (p < 0.001) as well kidney (p < 0.01) when compared with heavy metals group; that issue clarify the protective role of propolis in recovering the affected tissues of liver and kidney as healthy rats through reducing combined toxicity of investigated metals; these ndings were corroborated very well with Salama & El-Bahr, (2007);Bhadauria, (2012) and Mohamed et al, (2017).…”
Section: -4-antioxidant Enzymes and Propolissupporting
confidence: 67%
“…Reactive oxygen species (ROS) play roles in cellular pathogenesis, including testicular cells (Bas & Kalender, ; Guesmi et al., ). Fatty acids are crucial in maintaining sperm functions in male reproductive cells (Ozan, Kaya, Yılmaz, Erdem, & Ozan, ; Turner & Lysiak, ).…”
Section: Discussionmentioning
confidence: 99%
“…Male germ cells are more susceptible to oxidative stress than other cells, because they have higher polyunsaturated fatty acids in their membranes than somatic cells. Oxidative stress plays an important role in the aetiology of defective sperm formation, function, sperm count and male infertility (Bas & Kalender, ). In our study, we showed that diabetes was associated with an oxidative stress state evidenced by a significantly increased testicular MDA level (lipid peroxidation) in the untreated diabetic rats.…”
Section: Discussionmentioning
confidence: 99%